Pendampingan Pembuatan Formula Serbuk Lulur Body Scrub Beras Hitam Di Desa Bandungan Kecamatan Saradan Kabupaten Madiun Jawa Timur - Kharisma Jayak P; Dewi Weni S; Romio Carlos Lopo Dos Reis (AMMA : Jurnal Pengabdian Masyarakat, 2024)
Facing the modern era which is currently developing rapidly, especially in the use of black rice as a commodity, a new innovation is needed which aims to increase the economic value of black rice products in the Bandungan village. So far, black rice has only been used as a food product, so it must have innovation to be able to compete with products from other places. One effort to increase the added value of black rice products is to use black rice to make body scrub products. Black rice contains antioxidants which can accelerate collagen production and play a role in skin elasticity. The slightly rough texture of rice flour can be used as a facial scrub. Black rice contains several anti-oxidants, such as phytic acid and vitamin B and anti-oxidants help fight free radical damage and maintain healthy skin. so it is good for skin health, as well as body scrub preparations which can help smooth and remove dead skin cells on the body. The methods used in implementing community service activities are field survey, training, practice, discussion and question and answer methods targeting village residents, especially housewives, youth and Bandungan Village officials who want to maximize existing potential by making innovative body scrubs from rice. black. By holding community service activities through training in making black rice body scrub preparations, village residents can increase their knowledge and skills in processing black rice products in the cosmetic sector so that it is hoped that they can provide highly competitive added value, income for the community and improve the residents' economy.